Engineering characteristics of Ariake Clay (soft Quaternary deposits) from Saga Plain, Japan - Iwao, Y.; Gurung, N. (Journal of Nepal Geological Society, 2000)
The Saga Plain of Kyushu, Japan, is surrounded by mountains and the inland Ariake Sea. It consists of lowland soft deposits of Quaternary age around the big inland Ariake Sea. The Ariake Clay shows great variation in material thickness, sensitivity, and softness. The top clayey soil is generally 10 to 20 m thick. Clay minerals are represented by montmorillonite, illite, hydro halloysite and metahalloysite with a lot of diatom remains. Natural disasters such as landslides, subsidence, liquefaction, and flooding are frequent due to its inherent weak engineering properties. These characteristics are linked with many engineering problems for further infrastructure development. In the paper, quantitative correlations from a vast soil test database are briefly presented for each geographical location.